Toward Systematic Screening for Persistent Hepatitis E Virus Infections in Transplant Patients. Issue 7 (July 2018) - Ankcorn, Michael J.; Ijaz, Samreen; Poh, John; Elsharkawy, Ahmed M.; Smit, Erasmus; Cramb, Robert; Ravi, Swathi; Martin, Kate; Tedder, Richard; Neuberger, James
Abstract : Background: Persistent hepatitis E virus genotype 3 (HEV G3) infections affect solid organ transplant (SOT) recipients and hematopoietic stem cell transplant (HSCT) recipients, but the burden in these cohorts in the United Kingdom is unknown. We established an audit to determine the point prevalence of HEV viremia in SOT and HSCT patients in the United Kingdom and compare different testing approaches to inform screening strategies. Methods: Between January 5, 2016, and September 21, 2016, 3044 patients undergoing therapeutic drug monitoring at a single transplant center were screened for HEV ribonucleic acid (RNA) in minipools. A total of 2822 patients who could be characterized included 2419 SOT patients, 144 HSCT patients and 259 patients with no available transplant history. HEV RNA-positive samples were characterized by serology and genomic phylogeny. HEV antigen (HEV-Ag) testing was performed on RNA-positive samples, 420 RNA-negative samples and 176 RNA-negative blood donor samples. Results: Nineteen of 2822 patients were viremic with G3 HEV giving a prevalence of 0.67%. The median alanine aminotransferase was significantly higher in the HEV viremic patients ( P < 0.0001); however, 2 viremic patients had an alanine aminotransferase value within the normal range at the time of screening. The HEV-Ag assay identified 18/19 viremic patients and all those patients with proven viremia longer than 4 weeks. Conclusions: Transplant recipients in the United Kingdom are at a low but significant risk of HEV infection. HEV-Ag detection could be an alternative to RNA detection where the goal is to identify established persistent HEV infection, particularly where expertise, facilities, or cost prohibit RNA testing. Abstract : Transplant recipients in the UK are at a low but significant risk of hepatitis E virus (HEV) infection and HEV-Ag detection could be an alternative to RNA detection where the goal is to identify established persistent HEV infection.